Application of Molecular Diagnostics in Primary Detection of ESBL Directly from Clinical Specimens - Sittová, Martina; Röderová, Magdaléna; Dendis, Miloš; Hricová, Kristýna; Pudová, Vendula; Horváth, Radek; Růžička, Filip; Dosoudilová, Šárka; Kolář, Milan (Microbial drug resistance (Larchmont, N.Y.), 2015)
The infections caused by extended-spectrum β-lactamase (ESBL)-producing organisms are associated with increased mortality. The real-time polymerase chain reaction (PCR) method, which enables detection of ESBLs directly from patients' clinical material, was developed. This study focused on blaCTX-M and blaSHV determination in endotracheal aspirates. Each sample was identified with standard microbiological procedures and simultaneously analyzed for the presence of nucleic acids, which encode CTX-M and SHV ESBL enzymes using real-time PCR. A total of 341 samples were investigated. In the set, 27 ESBL-positive samples were identified by phenotypic methods, while 60 positive samples were identified by the PCR method. Of the 60 PCR-positive samples, 58 were positive for the blaCTX-M. In two samples, the ESBL blaSHV-ESBL gene was detected. One phenotypically positive sample was PCR negative. The real-time PCR assay does not require a cultivation step and therefore enables detection of ESBL in 6 hours. The rapid method is necessary for early and adequate antimicrobial treatment.
Keywords: Enterobacteriaceae; Respiratory Tract Infections; exprese genu; Gene Expression; Plasmids; retrospektivní studie; kvantitativní polymerázová řetězová reakce; beta-Lactam Resistance; antibakteriální látky; beta-Lactamases; Microbial Sensitivity Tests; enterobakteriální infekce; infekce dýchací soustavy; beta-laktamasy; Real-Time Polymerase Chain Reaction; Enterobacteriaceae Infections; lidé; Anti-Bacterial Agents; beta-laktamová rezistence; Humans; mikrobiální testy citlivosti; plazmidy; Retrospective Studies